PRIMA IS A NEW CULTIVAR OF VEGETABLE PEA - A. G. Besedin (Овощи России)
In 2013, the new vegetable pea cv.Prima was applied for the State Variety Trial. This variety is characterized by very yearly-ripeness, that allows to increase the raw material processing in the canning factories of the Kuban.